Induction of Complete Remission by Azacitidine in a Patient with Myelodysplastic Syndrome-Associated Inflammatory Bowel Disease. (14th December 2017) - Kono, Masashi; Komeda, Yoriaki; Sakurai, Toshiharu; Okamoto, Ayana; Minaga, Kosuke; Kamata, Ken; Hagiwara, Satoru; Inoue, Hiroaki; Enoki, Eisuke; Matsumura, Itaru; Watanabe, Tomohiro; Kudo, Masatoshi
Abstract: Myelodysplastic syndrome [MDS] is a clonal disorder of bone marrow [BM] cells, caused by acquired chromosomal abnormalities and gene mutations. Pro-inflammatory antigen-presenting cells [APCs] originating from BM cells bearing chromosomal abnormalities and gene mutations can cause immune-mediated disorders including inflammatory bowel disease [IBD]. Here, we report the first case with MDS-associated IBD that was successfully treated with the DNA methyltransferase inhibitor, azacitidine [AZA]. A 75-year-old man with a 5-year history of MDS was admitted for examination of diarrhoea and high fever. Blood examination revealed pancytopenia and a marked elevation of C-reactive protein. Colonoscopy revealed multiple round ulcers from the terminal ileum to the sigmoid colon. Pathological examination of the endoscopic biopsy specimens showed destruction of crypt architecture and infiltration of CD3 + T cells and CD68 + macrophages. Surprisingly, administration of AZA, which has been approved for the treatment of high-risk MDS, improved the symptoms, and the multiple round ulcers disappeared. AZA treatment markedly decreased the expressions of tumour necrosis factor-α, interleukin-12 (IL-12)/23p40 and IL-17 in colonic biopsy samples, as assessed by quantitative reverse transcription polymerase chain reaction. In contrast, AZA treatment did not change the expression of forkhead box P3, a master regulator of regulatory T cells. These data suggest that AZA treatment led to complete remission in MDS-associated IBD through suppression of pro-inflammatory cytokine responses.